Assessment of clinical continuity strategies offered by dual-degree training programs in the USA. Issue 1 (26th August 2022) - Spellicy, Samantha E.; Mannon, Elinor C.; Iness, Audra N.; Erickson, Hanna L.; Camacho, Mariam B.; Banerjee, Abhik; Liu, Jillian; Adami, Alex; Weintraub, Neal L.
Abstract: Background: Integration of clinical skills during graduate training in dual-degree programs remains a challenge. The present study investigated the availability and self-perceived efficacy of clinical continuity strategies for dual-degree trainees preparing for clinical training. Methods: Survey participants were MD/DO-PhD students enrolled in dual-degree-granting institutions in the USA. The response rate was 95% of 73 unique institutions surveyed, representing 56% of the 124 MD-PhD and 7 DO-PhD recognized training programs. Respondents were asked to indicate the availability and self-perceived efficacy of each strategy. Results: Reported available clinical continuity strategies included clinical volunteering (95.6%), medical grand rounds (86.9%), mentored clinical experiences (84.2%), standardized patients/ practice Objective Structured Clinical Examinations (OSCEs) (70.3%), clinical case reviews (45.9%), clinical journal clubs (38.3%), and preclinical courses/review sessions (37.2%). Trainees rated standardized patients ( µ = 6.98 ± 0.356), mentored clinical experiences ( µ = 6.94 ± 0.301), clinical skills review sessions ( µ = 6.89 ± 0.384), preclinical courses/review sessions (µ = 6.74 ± 0.482), and clinical volunteering ( µ = 6.60 ± 0.369), significantly ( p < 0.050) higher than clinical case review ( µ = 5.34 ± 0.412), clinical journal club ( µ = 4.75 ± 0.498), and medicine grand rounds ( µ = 4.45 ± 0.377). Further, 84.4% of respondents stated they would be willing to devote at least 0.5–1 hour per week to clinical continuity opportunities during graduate training. Conclusion: Less than half of the institutions surveyed offered strategies perceived as the most efficacious in preparing trainees for clinical reentry, such as clinical skills review sessions. Broader implementation of these strategies could help better prepare dual-degree students for their return to clinical training.